Rancang Bangun Traffic Light System Tanggap Darurat Berbasis IoT - Usman Usman; Panjaitan Albert; Indah Vusvita Sari; Iswandi Idris; Rizaldy Khair (STMIK Budi Darma, 2020)
At crossroads, both crossing three and crossing four which have traffic lights, there is often heavy traffic. Of course this can hamper the performance of priority vehicles that will cross the intersection. To overcome this, the researchers designed a traffic light microcontroller system using a sound sensor. Sound sensor is an automatic identification technology that uses sound waves that hit the sensor membrane which causes the sensor membrane to move which has a small coil behind the membrane up and down then the sensor will be connected to the lights at each airport parking road junction so that the traffic lights of the parking area and arrival terminal or the release changes automatically. The purpose of this study is expected to produce a traffic light system design that utilizes IOT sound sensor technology to the density of vehicles that are at a crossroads either intersection three or intersection four in order to regulate the smooth flow of vehicles and things emergency vehicles (ambulances, fire engines or officials) can work on time and at the maximum, The output produced is a prototype IoT product and publication to journal